MDM2 is a central node in the p53 pathway: 12 years and counting. - Bond, G; Hu, W; Levine, A (2005)
Twelve years ago, the Mdm2 oncogene was shown to bind to and inhibit the tumor suppressor protein, p53. During the past 12 years, both genetic and biochemical studies have demonstrated that Mdm2 is a key negative regulator of the tumor suppressor p53. Mdm2 and p53 form an oscillating auto-regulatory feedback loop, which is tightly controlled to allow the appropriate response to environmental stresses in order to suppress tumor formation. When Mdm2 activity is inappropriately heightened, as it is in many human tumors, p53 activity is attenuated and tumor susceptibility arises. The p53 gene is mutated in 50% of all human tumors, but in those tumors that retain wild type p53, inhibiting Mdm2 activity could activate p53 tumor suppression and therefore provide a therapeutic strategy for the treatment of cancer.